2017
DOI: 10.3389/fimmu.2017.01094
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Systemic Autoimmunity in the Absence of Somatic Hypermutation in 564Igi: A Mouse Model of Systemic Lupus with Knocked-In Heavy and Light Chain Genes

Abstract: 564Igi mice have knocked-in immunoglobulin (Ig) heavy (H) and light (L) chain genes that encode an autoantibody recognizing RNA. Previously, we showed that these mice produce pathogenic IgG autoantibodies when activation-induced deaminase (AID) is expressed in pre-B and immature B cells but not when it is expressed only in mature B cells. AID has two functions; it is necessary for somatic hypermutation (SHM) and class switch recombination (CSR). To determine the role of each of these functions in the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…In contrast to the prevailing view supported by others and us, which illustrates an essential role of SHM deficiency in SLE alleviation (8,25,26,37), a more recent work based on 564Igi mice reported that SHM deficiency caused by AID G23S accelerated lupus nephritis (39). Clearly, a major difference between these studies lies in distinct SLE mouse models.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast to the prevailing view supported by others and us, which illustrates an essential role of SHM deficiency in SLE alleviation (8,25,26,37), a more recent work based on 564Igi mice reported that SHM deficiency caused by AID G23S accelerated lupus nephritis (39). Clearly, a major difference between these studies lies in distinct SLE mouse models.…”
Section: Discussionmentioning
confidence: 66%
“…In bone marrow B cells, SHM controlled by AID participates in the regulation of central B cell tolerance through removing developing autoreactive B cells via receptor editing in autoreactive BCR (42)(43)(44). Owing to the lack of SHM in AID G23S 564Igi mice, inefficient removal of the developing autoreactive B cells led to the accumulation of pathogenic autoantibodies and thereby accelerated lupus nephritis (39). In the alternative MRL/lpr mouse model, created in a different manner and widely used in numerous studies, impaired fas gene expression blocks the Fas-FasL apoptotic pathway and thereby causes the persistence of activated B cells in periphery (29,30,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that clones that continue to mutate at high rates could acquire mutations that are detrimental to immunoglobulin structure 129 . Another explanation is that RF clones could acquire “redeeming” mutations that remove their IgG‐binding activity similar to that proposed for other autoreactive B cells 91,130 …”
Section: Pathogenic Autoantibody Developmentmentioning
confidence: 99%
“…In a 564Igi mouse model of SLE, a dosage difference in TLR8 determined the sex bias in anti-RNA IgG antibodies, which were higher in female than male mice (Umiker et al, 2014). 564Igi mice are especially susceptible to autoimmunity because of diminished somatic hypermutation (McDonald et al, 2017). The release of miR-21 due to neuropathy stimulates TLR8 signaling in the dorsal root ganglia, which leads to hyperexcitability and pain (Zhang et al, 2018).…”
Section: Sex Chromosomes and Immune-associated Genesmentioning
confidence: 99%